Grammarly and Grammatical Errors Reduction: A Case for Non-Native English Teachers’ Professional Learning - I G A Lokita Purnamika Utami; I Gusti Ngurah Agung Wijaya Mahardika (International Journal of Language Education, 2023)
Grammar has long been a source of aggravation for anyone learning a second language, not just English language learners, but also non-native English teachers. People can now employ Grammarly to correct their grammar mistakes, owing to the sophistication of modern technology. The debate over whether teachers use Grammarly as part of their professional development is ongoing. The purpose of this study was to identify the grammatical errors made by non-native English teachers when writing narrative texts before and after Grammarly checked them. The participants in this qualitative study were 24 English teachers from the English Teacher Association of Buleleng Regency in Bali, Indonesia. This study employed the surface approach taxonomy to analyze the grammatical errors and interviewed the teachers to elicit factors that contribute to grammatical errors. This study found that the most common type of misformation error, specifically the alternating form error, was found in both Grammarly-corrected and Grammarly-uncorrected texts. Furthermore, intralingual factors were responsible for the majority of errors. The integration of Grammarly into teachers' professional learning is discussed.